Circulating macrophage migration inhibitory factor (MIF) in patients with heart failure. (October 2018) - Luedike, Peter; Alatzides, Georgios; Papathanasiou, Maria; Heisler, Martin; Pohl, Julia; Lehmann, Nils; Rassaf, Tienush
Highlights: MIF can be detected in the circulation of patients with heart failure. MIF plasma levels don't vary between different heart failure subgroups. Increased MIF plasma levels show an association with the pulmonary artery systolic pressure. Increased MIF plasma levels might be associated with all-cause mortality in patients with heart failure. Abstract: Background: Heart failure (HF) is characterized by impaired systolic ejection capacity and/or diastolic filling of the heart, leading to a multisystem disorder. Remote organ failure, systemic inflammation or pulmonary hypertension (PH) are hallmarks of the pathophysiological changes in HF. The Macrophage migration inhibitory factor (MIF) is a pro-inflammatory cytokine that is involved in a variety of cardiovascular and inflammatory diseases. Circulating MIF levels and their potential role as a disease marker in the different subgroups of HF have not been investigated yet. We here aimed to unravel a potential role of MIF in HF. Methods and results: MIF plasma levels were assessed in 249 consecutive patients with HF. MIF was detectable in all investigated subjects and showed no difference with regard to the nature of HF (preserved or reduced ejection fraction). Spearman correlation revealed an association with inflammatory biomarkers (white blood cell count r = 0.18, p = 0.005; c-reactive protein r = 0.20, p = 0.003). MIF was associated with higher pulmonary artery systolic pressure (PASP) as assessed by echocardiography (r = 0.23, p < 0.001). Log-transformed PASP was also independently associated with MIF in a multivariable linear regression model (p = 0.02). Follow-up (FU) data after 180 days revealed that patients with increased MIF values (in ng/ml) were more likely to reach the endpoint all-cause mortality (HR 1.01, 95% CI 1.004–1.02, p = 0.005, per unit change). Conclusion: MIF is detectable in the circulation of patients with HF and might be associated with clinical endpoints in HF, markers of inflammation and PH. These promising results should stimulate further research to elucidate the role of MIF in the multisystem disorder of HF.